Effects of fluid and norepinephrine resuscitation in a sheep model of endotoxin shock and acute kidney injury - Ferrara, Gonzalo (2019)
The pathophysiology of renal failure in septic shock is complex. Although microvascular dysfunction has been proposed as a mechanism, there are controversial findings about the characteristics of microvascular redistribution and the effects of resuscitation. Our hypothesis was that the normalization of systemic hemodynamics with fluids and norepinephrine fails to improve acute kidney injury. To test this hypothesis, we assessed systemic and renal hemodynamics and oxygen metabolism in 24 anesthetized and mechanically ventilated sheep. Renal cortical microcirculation was evaluated by SDF-videomicroscopy. Shock (n = 12) was induced by intravenous administration of endotoxin. After 60 min of shock, 30 mL/kg of saline solution was infused and norepinephrine was titrated to reach a mean blood pressure of 70 mmHg for 2 h. These animals were compared with a sham group (n = 12). After endotoxin administration, mean blood pressure, cardiac index, and systemic O2 transport and consumption decreased (P < 0.05 for all). Resuscitation improved these variables. Endotoxin shock also reduced renal blood flow and O2 transport and consumption (205[157-293] vs. 131 [99-185], 28.4[19.0-38.2] vs. 15.8[13.5-23.2], and 5.4[4.0-8.8] vs. 3.7[3.3-4.5] mL·min-1·100 g-1, respectively); cortical perfused capillary density (23.8[23.5-25.9] vs. 17.5[15.1-19.0] mm/mm2); and creatinine clearance (62.4[39.2-99.4] vs. 10.7[4.4-23.5] mL/min). After 2 h of resuscitation, these variables did not improve (174[91-186], 20.5[10.8-22.7], and 3.8[1.9-4.8] mL·min-1·100 g-1, 19.9[18.6-22.1] mm/mm2, and 5.9[1.0-11.9] mL/min). In conclusion, endotoxin shock induced severe renal failure associated with decreased renal flow, O2 transport and consumption, and cortical microcirculation. Normalization of systemic hemodynamics with fluids and norepinephrine failed to improve renal perfusion, oxygenation, and function. New & noteworthy: This experimental model of endotoxin shock induced severe renal failure, which was associated with abnormalities in renal regional blood flow, microcirculation, and oxygenation. Derangements included the compromise of peritubular microvascular perfusion. Improvements in systemic hemodynamics through fluids and norepinephrine were unable to correct these abnormalities.